2009
DOI: 10.1038/modpathol.2008.181
|View full text |Cite
|
Sign up to set email alerts
|

Y-Box-binding protein-1 is a promising predictive marker of radioresistance and chemoradioresistance in nasopharyngeal cancer

Abstract: The Y-Box-binding protein-1, a member of the cold-shock domain DNA-and RNA-binding protein superfamily, is known to mediate chemoresistance. The aim of this study was to determine the expression of Y-Box- Y-Box-binding protein-1 immunostaining was observed to be predominantly cytoplasmic. A higher recurrence of nasopharyngeal cancer was found in patients whose tissues had increased Y-Box-binding protein-1 expression (Po0.001). The Cox proportionate hazard regression model also established that high Y-Box-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…It was reported that the expression of YB-1 increases in cancer cells and its high expression or expression in nucleus were associated with poor prognosis in many types of cancer [6–9, 13]. Also, this nuclear expression of YB-1 in tumor cell activates gene transcription for protein and relates to multidrug resistance and ionizing radiation [10, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the expression of YB-1 increases in cancer cells and its high expression or expression in nucleus were associated with poor prognosis in many types of cancer [6–9, 13]. Also, this nuclear expression of YB-1 in tumor cell activates gene transcription for protein and relates to multidrug resistance and ionizing radiation [10, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…vRNP was prepared from purified influenza A/Puerto Rico/8/34 (A/PR/8/34) virus as previously described (66). Rabbit polyclonal antibodies against YB-1, RAP55, RCK, PB1, PB2, PA, M1, and NP and rat antibody against NS2 were prepared as previously described (30,31,40,50,71,72,77). Rabbit polyclonal antibodies against TIAR, PML (Santa Cruz Biotechnology), and Rab11a (Invitrogen) and mouse monoclonal antibodies against ␣-tubulin (Sigma) and PML (Santa Cruz Biotechnology) were purchased.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unclear whether these molecules continue to be relevant as prognostic factors for patients with DLBCL who are treated with rituximab plus CHOP/CHOP-like chemotherapy. Meanwhile, in some reports, the expression of YB-1 in tumor tissues has been shown to be restricted to the cytoplasm [12,24], and no correlation has been found between the expressions of YB-1 and P-gp [20]. The role of YB-1 in predicting the outcome of malignant neoplasms is thus still unclear.…”
Section: Introductionmentioning
confidence: 92%